Exclusive Papers of the Editorial Board Members (EBMs) of the Materials Chemistry Section of Molecules - Cirillo, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book is intended to collect the recent contributions (either research or review papers) to the development of the "Materials Chemistry" research fields by the Editorial Board Members of the Materials Chemistry Section of Molecules. The aim is to present the recent progress in the fields and to highlight the key role of Materials Chemistry in a multidisciplinary research context.